Atomic Force Microscopy of host cell-amastigote interaction in cutaneous leishmaniasis - A Lugo de Yarbuh; C Colasante; M Alarcón; E Moreno (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2004)
Natural infection produced by the entry of promastigotes into the skin cells induces cutaneous leishmaniasis disease and the Interaction between phagocytic cells and different strains of Leishmania determine the course of disease in the mammalian host. In this study the cutaneous lesions from hamsters infected with the L. garnhami were pressed on amicroscope slide, allowed to dry and methanol-fixed in order to be ultrastructurally analyzed using atomic force microscopy (AFM). Free amastigotes showed their nucleus, kinetoplast and a depression of 5microns, corresponding to the refractil organelle characteristic of this Leishmania. Parasites inside macrophages and lymphocytes and the topographical relationship with the host cytoplasm was also observed. Parasite-host-cell interaction revealed different membrane contact. The amastigote-macrophage contact is established by small macrophage filopodio associated with its cytoplasmic reduction near the contact site of 800 nm. The amastigote-lymphocyte contact shows fusion-like behavior between the two membranes without any cell specialization. The cutaneous lesion studied with AFM allowed observation with high resolution the close contact established between the parasite and its host cells as well as details of the fine structure of the amastigotes, applying a simple and rapid tissue preparation.